The Unsteady Mainstay of the Family: Now Adult Children's Retrospective View on Social Support in Relation to Their Parent's Heart Transplantation - Susanna Ågren; Bodil Ivarsson; Helén Rönning (Hindawi Limited, 2014)
The needs for support among children with a seriously ill parent, who is waiting for heart transplantation, are unknown today. The aim was to describe now adult children's experiences of social support in relation to a parent's heart transplant during childhood. Nine females and four males were interviewed. The median age for the children was 18 at the transplantation and their parents had been ill before for 18 months (median) and on waiting list for 161 days (mean). Three categories emerged: health care professionals' approaches, family and friends' approaches, and society approaches. Our results show that there was lack of support for children of heart transplantation patients. Support in the shape of information was in most cases provided by the sick or healthy parent. It is of great clinical importance to develop psychosocial support programs for children with a seriously ill parent waiting for heart transplantation (before, during, and after surgery).